Sensing-Based Spectrum Sharing Method in Satellite-Terrestrial Network - Jing HU; Dongming BIAN; Xiang TIAN; Yinxia ZHU; Jian ZHANG (天地一体化信息网络)
Considering the spatial possibility of opportunistic spectrum sharing, sensing-based spectrum sharing method ws applied in the satellite-terrestrial network.The sensing-throughput tradeoff problem was studied, and the throughput is a concave function of the sensing duration was proved.In order to further improved the satellite uplink throughput, the multi-slots sensing method and the cooperative sensing method were proposed.Computer simulations showed that the optimal sensing duration could maximized the uplink throughput, and the multi-slot sensing method or the cooperative sensing method could further improved the throughput of satellite network.